2012
DOI: 10.1016/j.mito.2012.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Complementary RNA and protein profiling identifies iron as a key regulator of mitochondrial biogenesis

Abstract: SummaryMitochondria are centers of metabolism and signaling whose content and function must adapt to changing cellular environments. The biological signals that initiate mitochondrial restructuring and the cellular processes that drive this adaptive response are largely obscure. To better define these systems, we performed matched quantitative genomic and proteomic analyses of mouse muscle cells as they performed mitochondrial biogenesis. We find that proteins involved in cellular iron homeostasis are highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
5
25
1
Order By: Relevance
“…Because neurons require iron for mitochondrial biogenesis (30) and respiration (31), we examined mitochondrial morphology by electron microscopy, identifying DA neurons by immunogold localization of DAT. Although SNpc mitochondria appeared normal in 6-wk Tfr1-CKO mice, at 8 wk, they were enlarged with abnormal cristae (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because neurons require iron for mitochondrial biogenesis (30) and respiration (31), we examined mitochondrial morphology by electron microscopy, identifying DA neurons by immunogold localization of DAT. Although SNpc mitochondria appeared normal in 6-wk Tfr1-CKO mice, at 8 wk, they were enlarged with abnormal cristae (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Iron Deprivation Decreases Transcription of Nuclear DNAencoded Mitochondrial Genes-Our previous analyses revealed that iron deprivation initiates an adaptive cellular response involving a global decrease in transcripts encoding mitochondrial proteins and that this effect is especially strong for transcripts encoding subunits of the oxidative phosphorylation (OxPhos) complexes (23). However, the mechanism driving this response has not been determined.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, through the use of matched microarray and mass spectrometry-based proteomic approaches, iron deprivation was found to initiate an adaptive mitochondrial biogenesis response (23). Specifically, iron depletion, through chelation or active transport, caused a rapid and reversible decrease in the abundance of nuclear and mitochondrial transcripts encoding mitochondrial proteins that was equal and opposite in effect size to overexpression of the potent transcriptional co-activator PGC-1␣.…”
mentioning
confidence: 99%
“…At the cellular level, iron has been recently identified as a key regulator of mitochondrial biogenesis [16]. In fact, intracellular iron is used in the build-up of Fe-S clusters, which are necessary for the regulation of mitochondrial oxidative processes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to elucidate the effect of metabolic perturbation on iron metabolism during adipocyte differentiation, the effects of saturated fatty acids (palmitate) on these genes were also tested. Since iron is essential for mitochondrial biogenesis [16], and optimal mitochondrial biogenesis and function is a key component in adipocyte differentiation [18], we also analysed genes related to mitochondrial biogenesis in these experiments.…”
Section: Introductionmentioning
confidence: 99%